Pneumococcal Colonization in the Familial Context and Implications for Anti-Pneumococcal Immunization in Adults: Results from the BINOCOLO Project in Sicily - Tramuto, Fabio (Int J Mol Sci, 2017)
The spread of Streptococcus pneumoniae within families has been scarcely investigated so far. This feasibility study aimed to estimate the prevalence of pneumococcal carriage in school-aged children and co-habiting relatives and to explore the potential link between the family environment and the sharing of pneumococcal serotypes covered by the vaccine. Oropharyngeal samples of 146 subjects belonging to 36 different family groups were molecularly tested for pneumococcal detection and serotyping. The overall prevalence of pneumococcal carriage was 65.8% (n = 96/146), whereas it was higher among schoolchildren (77.8%, n = 28/36); subjects of seven years of age had the highest odds of being colonized (odds ratio, OR = 5.176; p = 0.145). Pneumococcal serotypes included in the 13-valent conjugate vaccine formulation were largely detected in the study population and multiple serotypes colonization was considerable. Factors relating to a close proximity among people at the family level were statistically associated with pneumococcal carriage (OR = 2.121; p = 0.049), as well as active smoking habit with a clear dose-response effect (ORs = 1.017–3.326). About half of family clusters evidenced similar patterns of carried pneumococcal serotypes and the odds of sustaining a high level of intrafamilial sharing increased with household size (ORs = 1.083–5.000). This study highlighted the potential role played by the family environment in sustaining both the circulation and horizontal transmission of pneumococcus.